RhD-induced immunogenetic disparity between mother and fetus: medical importance and economic effect of using molecular genetic technology - A. G. Konopliannikov; A. N. Toropovskii; D. A. Viktorov; Yu. V. Myakisheva; R. F. Burganova; A. V. Solovyev; A. V. Kazakova; V. B. Marinovskaya (IRBIS LLC, 2021)
Introduction. Here we discuss the problem of timely diagnostics and prevention of Rh-immunization of pregnant women as well as fetal hemolytic disease, which remains currently relevant, despite the existence of proven diagnostic, therapeutic and preventive methods.Aim: to assess the medico-economic efficiency of non-invasive prenatal diagnostics of using fetal Rh factor (rhesus D antigen, RhD) in maternal blood - a fetal RhD-genotyping.Materials and Methods. A retrospective observational study was conducted to analyze determining fetal Rh-factor in the blood samples from 4109 Rh-negative pregnant women observed in the 41 medical facilities of the Ulyanovsk region in the years 2018-2020. The fetal RhD level was determined by polymerase chain reaction at gestational age of ≥ 10 weeks. To assess testrelated medical effectiveness, there were examined sensitivity, specificity, predictive value of positive and negative data as well as diagnostic accuracy. The data collected during the study were compared with those obtained after delivery. To assess the economic efficiency, the difference between the cost of immunization and the cost of determining the fetal Rh factor level was determined.Results. A positive and negative fetal Rh-factor was detected in 67.26 % (n = 2793) and 32.74 % (n = 1316) cases, respectively. Diagnostic accuracy of the test system "Test-RhD" was 99.40 %, sensitivity - 99.84 %, specificity - 97.51 %, the prognostic value of a positive result was 99.43 %, the predictive value of a negative result - 99.28 % with low rate of false positive and false negative data. It was shown that our study allows to avoid unnecessary immunization costs for all Rh-negative pregnant women.Conclusion. Analysis of the diagnostic characteristics and cost-effectiveness of the RhD test evidences about high medical significance of the method described and allows to recommend its wider application.